Bilateral Developmental Dysplasia of the Hip: Does Closed Reduction Have a Role in Management? Outcome of Closed and Open Reduction in 92 Hips. Issue 4 (April 2019) - Tennant, Sally J.; Hashemi-Nejad, Aresh; Calder, Peter; Eastwood, Deborah M.
Abstract : Background: Bilateral developmental dysplasia of the hip (DDH) is believed to have a worse outcome than unilateral DDH with the optimal treatment unclear. To define indications for treatment we report a retrospective series of 92 hips (46 patients) who underwent closed reduction (CR) and/or open reduction (OR). Methods: A total of 58 hips in 29 patients underwent attempted CR using our standardized protocol. In the same 12 year time period, 54 hips in 27 patients underwent an OR. Outcome measures included resolution of acetabular dysplasia, need for further surgery, development of osteonecrosis (ON), and modified Severin Grade. Results: CR was successful in 57% of hips; in this group secondary surgery was required in 15% and ON was seen in 12%. In the OR group, 11% failed to stabilize and required further early surgery: ON rate was 15% overall, and secondary surgery was required in 5%. In Tonnis 2/3 hips younger than 2 years, Severin grading was comparable following CR and OR, with 92% and 90% graded as Severin 1, respectively. The rate of significant ON was higher after CR in Tonnis 2/3 hips (12%) than after OR (0%). Overall, Tonnis 4 hips did badly: 94% failed CR and following OR, further surgery for redislocation/residual dysplasia was required in 21%. Conclusions: CR can be successful in Tonnis 2/3 bilateral hips, with acceptable rates of secondary surgery, ON, and Severin grading, the latter equivalent to open reduction. Importantly, persisting with casting of a unilateral dislocation, to allow the contra-lateral hip to stabilize, does not have an adverse effect. CR is not advised in Tonnis 4 bilateral hips. Parents should be counseled that the outcome of surgery for bilateral hips is not as good as for unilateral DDH, particularly for Tonnis 4 hips which are more difficult to stabilize and more likely to require supplementary surgery even after open reduction. Level of evidence: Level IV—Therapeutic Study.